Religião à brasileira: vínculos religiosos múltiplos em um país relacional - Ruppelt, Marcos Augusto Nogueira (2021)
This study aims to identify elements that explain the migration of religious between different Brazilian organizations and the formation of multiple links with religions. For this, the reserach used of a varied composition of theories, involving sociology of religion, brazilian sociology and theory of neoinstitutionalism. This is an empirical research of an exploratory type, with a qualitative approach and content analysis. Among the theoretical findings and conclusions obtained, it is possible to highlight three: the Brazilian beliefs are individualized and allows combinations, reconciliations and simultaneity; the link can be for convenience (à la carte), institutionalized or intellectualized; and the accumulation of religious experiences is directly linked to the relational characteristic of Brazilian people.